2012
DOI: 10.5455/msm.2012.24.232-237
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Barometer Pressure and Incidence of Cerebrovascular Insult

Abstract: Introduction:The intention of this work is to research whether the link between the barometer pressure and the cerebrovascular insult (CVI) exists. The stroke is the first cause of non-traumatic disability and third illness by mortality in the majority of available relevant literature.Goals:Goal of the sudy was to research all the cases of the patients who suffered from the acute stroke in the Canton of Sarajevo and those who were treated in the pre-hospital phase by Emergency Medical Institute staff and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Many institutional or regional retrospective studies have examined the relationship between climate and aneurysmal subarachnoid hemorrhage, but the findings in the literature have been inconsistent. Prior research has suggested that ambient temperature, precipitation, sunlight, average humidity, and the lunar cycle may all be associated with an increased risk of rupture of cerebral aneurysms [4] , [5] , [10] [13] . On the other hand, others have found no associations between weather patterns and subarachnoid hemorrhage [3] , [8] , [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Many institutional or regional retrospective studies have examined the relationship between climate and aneurysmal subarachnoid hemorrhage, but the findings in the literature have been inconsistent. Prior research has suggested that ambient temperature, precipitation, sunlight, average humidity, and the lunar cycle may all be associated with an increased risk of rupture of cerebral aneurysms [4] , [5] , [10] [13] . On the other hand, others have found no associations between weather patterns and subarachnoid hemorrhage [3] , [8] , [9] .…”
Section: Discussionmentioning
confidence: 99%
“…E. Slatina и соавт. изучали влияние атмосферного давления на все виды инсульта и выявили, что небольшие колебания атмосферного давления значимо не сказываются на повышении риска развития инсульта и только экстремально низкие или экстремально высокие изменения атмосферного давления сопряжены с риском нарушений мозгового кровообращения [18].…”
Section: аневризматическое субарахноидальное кровоизлияние и метеорол...unclassified